Predicting freshwater production in seawater greenhouses using hybrid artificial neural network models - Panahi F.; Ahmed A.N.; Singh V.P.; Ehtearm M.; elshafie A.; Torabi Haghighi A. (Elsevier Ltd, 2023)
Climate models; Decision making; Evaporators; Forecasting; Greenhouses; Mean square error; Neural networks; Particle swarm optimization (PSO); Uncertainty analysis; Arid lands; Artificial neural network modeling; Decision makers; Fresh Water; Hybrid artificial neural network; Optimization algorithms; Seawater greenhouse; Semi-arid lands; Uncertainty; Water production; Seawater